Florida 4-H Food Challenge: Team Captain Guide - Geralyn Sachs (EDIS)
This guide will assist adults who are coaching teams to prepare for the Florida 4-H Food Challenge. It contains contest guidelines, suggested resources, scoresheets, and worksheet.